ANALISIS KOMITMEN PIMPINAN TERHADAP KESIAPAN PENERAPAN SISTEM MANAJEMEN K3 PADA SALAH SATU FAKULTAS KESEHATAN MASYARAKAT DI INDONESIA - Atikah Atikah; Ida Wahyuni; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Public health faculty X University is one of the working area that contain high level potential hazard which under working more than 100 workers. According to the characteristic, Public Health X university should implement safety and health management system according to Government Law No. 50 year 2012. However, until now, they have not already implemented safety and health management system. One of the fundamental principal to safety and health management system is commitment. The purpose of this research was to analyse how far the leader commitment towards institution readiness through implementation safety and health management system. The method of this research was qualitative research with in depth interview and observational approach. Interviews were conducted to top leader on public health faculty with triangulation to supportive party on safety and health management system faculty, such as Vice Dean II and Chairman of logistic and administration. Result showed that leader commitment form could be observed by resources through the availability of safety and health expertise, funding, facility and infrastructure, communication on safety induction or safety signates, and training to occupational safety and health student. No rules to regulate implementation safety and health management system in X University finally made the implementation of safety and health management system were not become the priority. Public Health Faculty X can make initiation to implement safety and health management system around X University with safety communication, safety maintenace, and emergency response preparedness simulation.